Numbers/Data: A Roundtable. (December 2017) - Connor, Steven; Corby, Tom; Nafus, Dawn; Hawes, Hannah Redler; Smith, Marquard; Teasley, Sarah
This Roundtable on Numbers/Data began life as a live, public event on the power and influence of numbers in contemporary visual, material, immaterial, and media cultures. 1 To imagine such an ambitious event, and to do it justice, the event's programme brought together academics, industry professionals, and practitioners. Taking Steven Connor's recently published book Living by Numbers: In Defence of Quantity (2016) as a springboard, each contributor to the event was invited to deliver a 10-minute presentation, an opening statement to set the scene, and to raise fundamental questions to be considered in the ensuing discussion. The authors retain this structure here, along with some of the informality that live conversation affords. By way of these four presentations and the conversation between the event's speakers and audience, the Roundtable raises a series of pressing concerns around data and big data, life tracking, digital health studies, and the quantifiable self; the quantitative and the qualitative; data forms and flows; climate change data and social media; the bleed between private and public computational infrastructures; labour, productivity, and accountability; time, money, and economies; and the contemporary intensification of surveillance, audit culture, marketization, and outcomes-based performance management. Notwithstanding data dystopia's numerical sublime, the contributors are always looking to keep an eye out for reasons to be optimistic in their discussions around: numbers in education and numeric literacies; the materiality of numbers and numbers as artifacts; data's flexibility and manipulability; sensors, sensor data, and everyday life; the rise of amateurism and citizen scientists; data and numbers vis-à-vis experiences, embodiment, emotions, intensities, and their affective powers; and the contributors' absolute delight (or abject horror) at the very arbitrary nature of numbers, all of which offer hope towards more democratic, creative, imaginative, and personalized futures … Interested in the Quantified Self community? Ever wondered what role numbers played in the UK's Referendum to leave the EU? Intrigued by the idea of an exhibition about odd and even? Curious about what folk data might be? Read on!